Removal of Pb(II) from aqueous solution using KCC-1: Optimization by response surface methodology (RSM) - Rosalyza, Hasan (Elsevier Ltd, 2018)
The performance of KCC-1 as adsorbent towards Pb(II) removal was investigated. The TEM, XRD, FTIR, and BET results proved that the synthesized KCC-1 contains fibrous silica structure with the surface area of 298.87 m2/g. The influence of prominent factors (initial concentration (X1), time (X2) and adsorbent dosage (X3)) on Pb(II) removal was evaluated by response surface methodology (RSM). The most significant factor was the linear function of adsorbent dosage (X3), while the quadratic effect of time (X22) was the least significant factor. Maximum Pb(II) removal of 84.54% predictably and 83.06% experimentally were achieved under the optimal conditions (X1 = 281.7 mg/L, X2 = 80 min and X3 = 3.7 g/L). The feasibility of KCC-1 in Pb(II) removal was confirmed by its good performance during five cycles of reusability study. It is affirmed that the KCC-1 has a high potential to be used in adsorption of Pb(II) from aqueous solution.